2014
DOI: 10.17843/rpmesp.2014.314.119
|View full text |Cite
|
Sign up to set email alerts
|

Neoplasia escamosa de la superficie ocular en pacientes con pterigión en Perú

Abstract: Objetivos. Estimar la frecuencia de neoplasia escamosa de la superficie ocular (NESO) no sospechada en pterigión, la precisión del diagnóstico clínico y las características demográficas y clínicas asociadas. Materiales y métodos. Se examinaron los informes histopatológicos de los pacientes con diagnóstico clínico de pterigión y/o NESO que fueron quirúrgicamente tratados entre marzo de 2009 y diciembre de 2012 en el Instituto Nacional de Oftalmología en Lima, Perú. La precisión del diagnóstico clínico para iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…A study performed in Lima, Peru, observed a 0.66% frequency of OSSN from 2891 samples clinically diagnosed pterygium. 23 A study from Toronto, Canada, of 1127 consecutive pterygia specimens over an 8year period, observed no cases of OSSN in their cohort. 24 Prolonged UV radiation through sunlight exposure has been implicated in the pathophysiology of both OSSN and pterygium.…”
Section: Discussionmentioning
confidence: 98%
“…A study performed in Lima, Peru, observed a 0.66% frequency of OSSN from 2891 samples clinically diagnosed pterygium. 23 A study from Toronto, Canada, of 1127 consecutive pterygia specimens over an 8year period, observed no cases of OSSN in their cohort. 24 Prolonged UV radiation through sunlight exposure has been implicated in the pathophysiology of both OSSN and pterygium.…”
Section: Discussionmentioning
confidence: 98%